Toxicological evaluation of long-term intravenous administration of amitraz in horses - Queiroz-Neto, A. [UNESP]; D'Angelis, F.H.F. [UNESP]; Harkins, J.D.; Tobin, T. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2002)
Estudou-se a possível toxicidade do uso prolongado do amitraz em eqüinos utilizando-se seis éguas Puro Sangue Inglês, as quais receberam injeções intravenosas de amitraz (0,05, 0,10 ou 0,15 mg/kg) semanalmente, durante quatro meses (grupo experimental). Outros oito animais (grupo-controle), seguindo o mesmo esquema de administração e período, receberam o veículo dimetilformamida. Ao final desse período colheram-se amostras de sangue dos animais e compararam-se as médias dos valores obtidos para as seguintes variáveis do sangue: hemograma completo, fosfatase alcalina, gama-glutamiltransferase, nitrogênio uréico, desidrogenase láctica, aspartato aminotransferase, creatina fosfoquinase, glucose, albumina, proteína total, creatinina, Na+ , K+, Cl- e CO2. Apenas as médias dos valores de nitrogênio uréico dos animais submetidos ao tratamento com amitraz foram diferentes das médias dos valores obtidos para o grupo-controle. As análises das características hematimétricas mostraram que não houve diferenças significativas quando se compararam os dois grupos. As dosagens de eletrólitos no sangue também demonstraram que o tratamento prolongado com amitraz não causou alterações significativas nas características analisadas. O amitraz na dosagem empregada não induziu efeitos tóxicos sobre órgãos vitais, mesmo após administração prolongada.

With the aim of determining the possible toxicity of amitraz after its prolonged use in horses, six English Thoroughbred horses received intravenous injections of amitraz (0.05, 0.10 or 0.15 mg/kg) weekly for four months, constituting the experimental group. Eight other animals (control group), via the same route following the same drug administration schedule and period of time, received the vehicle, dimethylformamide. At the end of this period, blood was collected from all the animals, and a comparison was made of the means of the values obtained for the various blood analyses: complete hemogram, alkaline phosphatase, gamma-glutamyltransferase, blood urea nitrogen, lactate dehydrogenase, aspartate aminotransferase, creatine phosphokinase, glucose, albumin, total protein, creatinine, Na+ , K+, Cl- and CO2. The results for the biochemical characteristics showed that only the mean value for urea of the animals submitted to treatment with amitraz was significantly different than the mean value obtained for the control group. The analyses of the hematological characteristics showed that no significant differences between groups were observed. Similarly, the measurement of blood electrolyte levels demonstrated that long-term treatment with amitraz did not cause significant changes in the variables analyzed. The results indicate that amitraz, given in the doses employed in this study, did not show signs of inducing toxic effects in vital organs, even after prolonged administration.
Avaliação toxicológica da administração intravenosa crônica de amitraz em eqüinos
Keywords: Horse; English Thoroughbred; Amitraz; Toxicity; blood characteristics; Electrolytes; Cavalo Puro Sangue Inglês; Amitraz; Toxicidade; variáveis sangüíneas; Eletrólitos